Exploring challenges and support structures of mothers with children with Autism Spectrum Disorder in the United Arab Emirates. (January 2022) - Lamba, Nishtha; Van Tonder, Angelique; Shrivastava, Anita; Raghavan, Archana
Highlights: Pandemic aggravated behavioral issues in children and distress in mothers. Dissatisfaction due to unclear and delayed diagnoses, often due to comorbidities. Mothers initially struggled to find appropriate interventions and schools. Support groups were beneficial, but there was less support from family members. Study recommends centralized information channels for expat parents in the UAE. Abstract: Background: Mothers with children with ASD, often being primary caregivers, experience high levels of parenting stress and hold essential information about their children's wellbeing. There is however lack of information about their experiences in the UAE. Aims: The study aims to explore challenges and support structures of mothers with children with ASD in the UAE. Methods and procedures: 17 expat mothers (Age range = 33-58 years) with a child with ASD were interviewed about their experiences with diagnoses, therapeutic interventions, support networks, and the pandemic. Outcomes and results: Thematic analysis showed that initially most mothers struggled with accessing information to seek correct diagnoses, admission in mainstream international schools with typically developing children, and finding appropriate therapeutic services. Several mothers narrated experiences of not receiving optimum support from their partners, feeling rejected from extended family members, and facing hardships during the pandemic. Majority however appeared to be extremely satisfied with support groups where they felt heard and exchanged experience-based information crucial for children's wellbeing. Conclusions and implications: Findings highlight the need for the government to facilitate centralized channels of information for expat parents with children with developmental disabilities, formalizing more support groups for mothers in the UAE, and increasing knowledge about autism to decrease biases.